Nigam’s standardization of manual anal dilatation (Lord’s procedure) - Nigam, Vinod K.; Nigam, Siddharth (International Surgery Journal, 2023)
Background: Standardisation of manual anal dilatation. It was a quality improvement study. Patients were admitted in various hospitals of Gurgaon, Haryana, India. Methods: Two hundred thirty-six patients of fissure in ano were treated by manual anal dilatation (Lord’s procedure) as per Nigam’s standardization between January 2010 and January 2022. Informed consent was obtained from each patient. All patients were evaluated for post procedure for complications. Two hundred thirty-six patients of fissure in ano were treated by manual anal dilatation (Lord’s procedure). Results: No patient developed faecal incontinence. Pain subsided immediately in all patients. No patient had non healing of anal fissure. Two patients had mild gas incontinence which resolved after 3-4 days. None of the patients required lateral sphincterotomy or fissurectomy. Most of the patients healed completely within three weeks. Conclusions: If manual anal dilatation is performed slowly, gently with controlled force for four minutes, as per Nigam’s standardisation then results are very good. This study includes patients of acute and chronic fissure in ano. The study excludes cases of anal cancer, stage III and IV haemorrhoids and inflammatory bowel disease.